IMPLEMENTASI NILAI DAN NORMA SOSIAL DALAM KEHIDUPAN MASYARAKAT DI DUSUN 2 DESA TANJUNG REJO - Putra Rabial Sibarani; Felix Agrian Brahmana, Fifi Fatiha; Muhammad Fahrul Zikri, Julia Ivanna (STKIP Subang, 2026)
Social values ​​and norms play a central role in creating order and harmony in community life, particularly in rural areas. This study aims to describe how social values ​​and norms are applied in the daily lives of the people of Hamlet 2, Tanjung Rejo Village. A descriptive qualitative approach was used, with data collected through in-depth interviews with one key informant. The research findings indicate that the community still highly values ​​mutual cooperation, deliberation, and adherence to customary and formal regulations. Furthermore, the involvement of generations in maintaining security and social maintenance is also quite significant. Based on these results, it can be concluded that social values ​​and norms remain important guidelines in maintaining harmony, stability, and solidarity in rural community life.